La economía política de la investigación en ciencias sociales en América Latina - Durán-Martínez, Angélica; Sierra, Jazmin; Snyder, Richard (El Colegio de México, 2023)
This article explores cross-national variation in funding for social science research by analyzing original bibliometric and survey data from Argentina, Colombia, and Peru. We identify three models of research based on whether foreign, domestic-public, or domestic-private funding prevails: foreign-sponsored, state-sponsored and mixed economy. We further find that each model is associated with distinct patterns of access to funding, the kind of knowledge produced, and researcher perceptions of their autonomy.